Isolation of phagocytes and effects of B. Glucan on the cellular immune response in grouper (Epinephelus Coioides). - Lopez, Rodney Villalobos
The use of immunostimulant is an alternative approach in controlling fish diseases. Studies have shown that B-1,3 glucan as immunostimulant could increase the cellular immune defenses in fishes by enhancing the phagocytic, respiratory burst, and bacterial killing of effector cells. Howver, its immunostimulatory effect in grouper Epinephelus spp. still remains to be investigated., This study investigates the ability of B-glucan in increasing the cellular immune response in grouper. This was accomplished by intraperitoneally injecting B-1,3 glucan Curdlan to grouper Epinephelus coioides at various doses, namely 0.5, 5.0, 10, 20 and 50 mg./kg body weight of fish. Seven days post injection, the swim bladder was injected with prepared neutrophil lysate after which the induced inflammatory swim bladder phagocytes were collected after four days post injection and used as effector cells. The phagocytic, respiratory burst, and bacterial killing activities of the swim bladder phagocytes were measured after its isolation. Microscopic examination of smears reveals most phagocytes collected were macrophages. Incubation of these cells with opsonized-zymosan particles showed a significant increase in the phagocytosis of opsonized-zymosan in Curdlan treated fish. The respiratory burst activity was also increased when the superoxide anions was measured using NBT. However, a significant reduction in the respiratory burst activity was observed when membrane stimulant phorbol myristate acetate (PMA) was added compared to the "untreated "PMA" cells. The ability macrophages to kill engulfed Vibrio anguillarum bacetria was likewise enhanced in glucan treated fish. Significant bacterial killing was observed when the macrophages are incubated to the bacteria for five hours as compared to incubation at 3 hours. In general, Curdlan significantly increased the cellular immune functions of the inflammatory macrophages. Enhanced cellular immune responses were observed in fish injected with 5 mg/kg of the glucan. It was noted that these responses rose in a dose-dependent fashion that peaked at 5 mg/kg and declined at 50 mg/kg doe. This suggest that intraperitoneal injection of B-1,3 glucan Curdlan at a dose of 5 mg/kg body weight can enhance the cellular immune responses in grouper, and raise our hope of using immunostimulants as viable alternative in increasing the immune competence and resistance of grouper to diseases.